Synthesis of esterified solid fat from fractionated rapeseed oil and palm stearin modeling by response surface methodology (Journal of the Bangladesh Agricultural University, 2012)
The main purpose of the study was to produce esterified solid fat (ESF) from fractionated rapeseed oil and palm   stearin through lipase-catalyzed reaction. The response surface methodology (RSM) was applied for optimization of   three reaction factors such as substrate mole ratio, enzyme percent, and reaction time. The design was adequate   and reproducible due to satisfactory levels of coefficient of determination (R2, 0.98) for both cases and coefficient   variation (CV, 4.06 for SFC at 10 °C and 7.95 for SFC at 30 °C, respectively). The substrate mole ratio was the   significant term for affecting the response of SFC (P